Simulation and Analysis of Power Spectral Density for Digital Pulse Interval Modulation (International Journal of Engineering and Computer Science, 2017)
In free space optical communication the signal power is changing with the bandwidth therefore PSD curves are very important in the link design. The power spectral density(PSD) of intensity modulation scheme i.e. Digital Pulse Interval Modulation (DPIM) has been presented. Results which are generated by simulations of an experimental system are presented. Which shows that DPIM has higher transmission capacity compared with digital pulse position modulation (DPPM) and is less complex to implement